Emotional learning and the development of differential moralities: implications from research on psychopathy. (24th September 2013) - Blair, R. James R.; White, Stuart F.; Meffert, Harma; Hwang, Soonjo
Abstract : In this paper, we will argue that (1) four classes of norm can be distinguished from a neuro‐cognitive perspective; (2) learning the prohibitive power of these norms relies on relatively independent emotional systems; (3) individuals with psychopathy show selective impairment for one of these emotional learning systems and two classes of norm: care based and justice based; and (4) while emotional learning systems are necessary for appropriate moral development/reasoning, they are not sufficient for moral development/reasoning.